"What have you done for me lately?" Re-thinking local representation. (December 2021) - Decadri, Silvia
Abstract: Scholars have studied the influence that constituents exert on elected representatives' action in national parliaments at length. Still, academic pundits have usually confined local representation to distributive policies and casework, and limited local legislators' focus to a territorial perspective. In this study, I try and propose a more nuanced theory of local representation, and I use automated text analysis to capture elected representatives' propensity to serve functional as well as territorial interests. In an effort to provide empirical backing to my theoretical argumentation, I present an analysis of Italian legislators' behavior which shows that deputies are willing to divert public spending to their district but also to favor the interests of specific economic sectors. Scholars have already acknowledged the multidimensional character of political representation at the national level, my analysis offers theoretical justification and empirical evidence to support doing so at the local level as well.